New strategic insights into managing fungal biofilms - Borghi, Elisa; Morace, Giulia; Borgo, Francesca; Rajendran, Ranjith; Sherry, Leighann; Nile, Christopher; Ramage, Gordon (Frontiers in Microbiology, 2015)
Fungal infections have dramatically increased in the last decades in parallel with an increase of populations with impaired immunity, resulting from medical conditions such as cancer, transplantation or other chronic diseases. Such opportunistic infections result from a complex relationship between fungi and host, and can range from self-limiting to chronic or life-threatening infections. Modern medicine, characterized by a wide use of biomedical devices, offers new niches for fungi to colonize and form biofilm communities. The capability of fungi to form biofilms is well documented and associated with increased drug tolerance and resistance. In addition, biofilm formation facilitates persistence in the host promoting a persistent inflammatory condition. With a limited availability of antifungals within our arsenal, new therapeutic approaches able to address both host and pathogenic factors that promote fungal disease progression, i.e. chronic inflammation and biofilm-formation, could represent an advantage in the clinical setting. In this paper we discuss the antifungal properties of Myriocin, Fulvic Acid and Acetylcholine in light of their already known anti-inflammatory activity and as candidate dual action therapeutics to treat opportunistic fungal infections.